The role of CD4-Lck in T-cell receptor antagonism: evidence for negative signaling. - Racioppi, L (1996)
Small changes in the complex between a peptide and a molecule of the major histocompatibility complex generate ligands able to partially activate (partial agonist) or even inhibit (antagonist) T-cell functions. T-cell receptor engagement of antagonist complex results in a partial zeta chain phosphorylation without activation of the associated ZAP-70 kinase. Herein we show that, despite a strong inhibition of both inositol phospholipid hydrolysis and extracellular increasing antagonist concentrations increased the activity of the CD4-Lck kinase. Addition of anti-CD4 antibody to culture medium prevented inhibitory effects induced by antagonist ligand. We propose that CD4-Lck activation triggered by antagonist complexes may act in a dominant negative mode, thus overriding stimulatory signals coming from agonist ligand. These findings identify a new T-cell signaling profile that may explain the ability of some T-cell receptor variant ligands to inhibit specific biological activities or trigger alternative activation programs.